Influence of sustained submaximal clenching fatigue test on electromyographic activity and maximum voluntary bite forces in healthy subjects and patients with temporomandibular disorders. (27th March 2017) - Xu, L.; Fan, S.; Cai, B.; Fang, Z.; Jiang, X.
Summary: This study aimed to investigate whether the fatigue induced by sustained motor task in the jaw elevator muscles differed between healthy subjects and patients with temporomandibular disorder (TMD). Fifteen patients with TMD and thirteen age‐ and sex‐matched healthy controls performed a fatigue test consisting of sustained clenching contractions at 30% maximal voluntary clenching intensity until test failure (the criterion for terminating the fatigue test was when the biting force decreased by 10% or more from the target force consecutively for >3 s). The pre‐ and post‐maximal bite forces (MBFs) were measured. Surface electromyographic signals were recorded from the superficial masseter muscles and anterior temporal muscles bilaterally, and the median frequency at the beginning, middle and end of the fatigue test was calculated. The duration of the fatigue test was also quantified. Both pre‐ and post‐MBFs were lower in patients with TMD than in controls ( P < 0·01). No significant difference was found in the percentage change in MBF between groups. The duration of the fatigue test in TMD patients was significantly shorter than that of the controls ( P < 0·05). Our results suggest that, compared to healthy subjects, patients with TMD become more easily fatigued, but the electromyographic activation process during the fatigue test is similar between healthy subjects and patients with TMD. However, the mechanisms involved in this process remain unclear, and further research is warranted.